Determinação de sacarose no xarope artificial de groselha por medidas de viscosidade: uma abordagem interdisciplinar - Monteiro, Marco Aurélio Alvarenga [UNESP]; Vaz, Ednilson Luiz Silva; Sampaio, Matheus De Moura; Codaro, Eduardo Norberto; Acciari, Heloisa Andréa (Universidade Federal de Santa Catarina (UFSC), 2013)
The development of the National Curriculum Parameters for High School (PCN) is established from a logic in which the disciplines are integrated and coordinated in order to promote interdisciplinarity. However, there are few didactic-pedagogic activities that enable teachers in practice to reach this goal. In this paper, we propose an experimental activity to be used with High School students, addressing the concept of viscosity from an interdisciplinary perspective between the disciplines of Physics and Chemistry. For that purpose, flow times of sucrose solutions of different concentrations will be measured in a glass Ford and these data will be used to construct a calibration curve, which will be used to determine the concentration of sucrose in artificial flavor syrup of gooseberry.

Os Parâmetros Curriculares Nacionais para o Ensino Médio propõem que o desenvolvimento curricular se estabeleça a partir de uma lógica na qual as disciplinas estejam integradas e articuladas de modo a favorecer a interdisciplinaridade. Contudo, são poucas as atividades de caráter didático-pedagógicas que possibilitam aos professores, na prática, a concretizarem esse objetivo. Neste trabalho, propõe-se uma atividade experimental para ser desenvolvida com alunos do Ensino Médio, abordando o conceito de viscosidade a partir de uma perspectiva interdisciplinar entre as discipli-nas de Física e Química. Para tal fim, os tempos de escoamento de soluções de sacarose de diferentes concentrações serão medidos em um copo Ford e os dados obtidos serão usados para a constru- ção de uma curva de calibração, que será usada para medir a concentração de sacarose no xarope artificial.
Keywords: Viscosity; Sucrose; Interdisciplinarity; Viscosidade; Sacarose; Interdisciplinaridade